Geological Heritage of the Republic of Macedonia as a Chalenge for the Development of Geoparks (Natural Resources and Technology, 2016)
Owing to the favorable geographic location, complexity of thegeological composition, versatile and specific natural characteristics, agrarian,demographic, ethnic and other characteristics Macedonia has always been aninteresting area for description and study.Natural and scientific studies of Macedonia carried out in the XIX centuryare different regarding the subject, content and methodology.The most common literary form used was description or descriptiveanalysis of the issues. Travel writings over the past, although small in numberare of importance.If we leave out fragmentary description on the natural-geographiccharacteristics in travel and other reports, it can be said that individual studiesdid not exist in the XIX century. A longer work published at the time was“Geographie physique de la Macedoine” published by Carlovitz (Paris, 1881).The period from the beginning of the XX century to the Balkan Wars(1912) marked the beginning of the study of the entire character of the areaof Macedonia. The most important study as a regional-geographic nature thatwill be used by many generations of research workers during the whole periodof the XX century is the long Monograph of Cvijic entitled The Element ofGeography and Geology for Macedonia and Old Serbia (Belgrade, 1906 -1911).